New Colombian Goja Navás (Psocodea: ‘Psocoptera’: Epipsocidae) with peculiar genitalia, and the first Goja with brachypterous male, from Oaxaca, Mexico - Carrejo, Nancy; Obando, Ranulfo González; Casasola-González, José Arturo; Aldrete, Alfonso N. García (Zootaxa, 2021)
Eight species of Goja are here described and illustrated, seven of them are from Colombia, they present peculiar phallosomes and constitute assemblages of three and four related species each, they are: G. andina n. sp., G. garridoi n. sp., G. meremberg n. sp., G. risaraldensis n. sp., G. tenerife n. sp., G. vallecaucana n. sp. and G. vavilovi n. sp. The other species, G. sierrajuarez n. sp., collected in the Sierra Juárez of Oaxaca, Mexico, is the first species of Goja, in which the male is brachypterous. A key to the identification of the males here treated is included, as well as a cladistic analysis of the species of Goja known to date.